Managerial accounting - Whitecotton, Stacey; Libby, Robert; Phillips, Fred , 1918- (McGraw-Hill Irwin, 2011)
Teaching Managerial Accounting in the Context of Business Whitecotton 1e addresses the reality of students taking the managerial accounting course: the majority of them will not become accounting majors and accountants; instead they will use accounting information in their professional lives to make business decisions. Therefore, the greatest challenges instructors have are to engage these students in the managerial accounting course, keep the students motivated throughout the course, and teach them accounting in a way that connects conceptual understanding to the real world, so students will be able to analyze and apply their managerial accounting knowledge successfully in careers as managers in the world of business. Whitecotton 1e will engage and motivate students by presenting accounting in the context of real, recognizable companies like Starbucks, Mattel, and Tombstone Pizza, then integrate those companies throughout the chapters. This will allow students to see accounting information being used to make real business decisions in companies that are part of their lives, helping them connect their learning to the real world